General principles for ensuring the openness and transparency of public authorities in Ukraine - Tymofieiev, Serhij (Public Administration and Regional Development, 2021)
The article is devoted to the study of the general principles of ensuring openness and transparency of public authorities and establishing the peculiarities of the implementation of these principles in Ukraine at the present stage. It is noted that the advantages of the decentralized model of public administration include a real form of local democracy in accordance with democratic principles of governance, taking into account the interests and needs of the local community, effective and rapid solution of local problems, disposal of own resources, financial independence. Analyzing the current stage of the process of building a management system at the local level, it can be noted that it takes place with the active involvement of the local community, taking into account their suggestions and discussions, which is mandatory for recognizing the legality of the process and making a final decision. It is determined that the main features of developed local self-government are ensuring transparency and openness; widespread use of direct democracy; accessibility for citizens’ appeals and feedback; minimized level or no corruption. The main directions of realization of the principles of transparency and openness of activity of public authorities are determined: objective and comprehensive consideration of appeals; consulting with civil society representatives; conducting communication activities; systematic activities in public relations. It is noted that the level of transparency and openness may change over time. Transparency of public authority can be interpreted in several ways: as a means of accountability of power, as a regulatory measure, as a means of improving efficiency. Regarding the characterization of transparency as a means of accountability of the government, this principle manifests itself in the reporting of public bodies, officials, involvement in public decision-making. It is noted that the public authorities have the task to ensure the principles of transparency and openness in the activities of their bodies.